Application of the input-output model for structural analysis on the example of the agricultural sector in Poland - Czyżewski Andrzej; Grzelak Aleksander (Management, 2018)
The main objective of the article is to recognize possibilities of use of the input-output model to structural assessments in the economy, with particular reference to the agricultural sector. The included considerations have a theoretical and application dimension related to the agricultural sector. Understanding the nature of structural changes and associated tendencies is particularly useful in shaping the economic policy of the state about the use of non-automatic economic stabilizers and the identification of areas that constitute development barriers. Analysis of the case of the agricultural sector in the input-output model, from the perspective of structural evaluation, indicate that there are evident transformations. It includes, in particular, the relative increase of links between agriculture and other branches, the growth in the importance of imports (supply), and the decline in the role of self-supply. It can be expected that these trends will deepen under conditions of economic development.